The influence of fault geometry on small strike-slip fault mechanics. (April 2015) - Ritz, Elizabeth; Pollard, David D.; Ferris, Michael
Abstract: Meter-scale subvertical strike-slip fault traces in the central Californian Sierra Nevada exhibit geometric complexities that significantly contribute to their mechanical behavior. Sections of faults that opened at depth channelized fluid flow, as evidenced by hydrothermal mineral infillings and alteration haloes. Thin sections show a variation in the style of ductile deformation of infill along the fault, with greater intensities of deformation along restraining bends. Orthorectified photomosaics of outcrops provide model geometries and parameter constraints used in a two-dimensional displacement discontinuity model incorporating a complementarity algorithm. Model results show that fault shape influences the distribution of opening, and consequently the spatial distribution of fluid conduits. Geometric irregularities are present at many scales, and sections of opening occur along both releasing and restraining bends. Model sensitivity tests focus on boundary conditions along the fault: frictional properties on closed sections and fluid pressure within sections of opening. The influence of the remote stress state varies along a non-planar fault, complicating the relationships between remote stresses, frictional properties, slip, and opening. Discontinuous sections of opening along model faults are similar in spatial distribution and aperture to the epidote infill assemblages observed in the field. Highlights: Field observations document where non-planar fault geometry leads to fault opening. Two styles of opening are distinguished: rhombochasms and lenses. Numerical modeling focuses on the mechanics of opening and slip. Roles of fluid pressure, frictional strength and coefficient of friction evaluated. Non-planar fault geometry complicates relationship of frictional properties.